Comparison of femoral stem subsidence between three types of press‐fit cementless total hip replacement in dogs. Issue 4 (21st February 2020) - Mitchell, Megan M.; Hudson, Caleb C.; Beale, Brian S.
Abstract: Objective: To compare femoral stem subsidence and determine contributing factors in dogs undergoing total hip replacement (THR) with the traditional BFX, collared BFX, and BFX lateral bolt stems. Study design: Retrospective radiographic study. Sample population: Ninety‐three dogs with 101 THR including dogs undergoing THR with a BFX lateral bolt femoral stem (n = 40), BFX collared stem (n = 21), and traditional BFX stem (n = 40). Methods: Radiographs of traditional BFX (n = 40), collared BFX (n = 21), and BFX lateral bolt (n = 40) THR performed from 2015 to 2018 were reviewed. Subsidence, canal flare index (CFI), stem canal fill (CF), stem orientation, and complications confirmed on radiographs were recorded at postoperative and recheck radiographs. Analysis of variance tests were used to compare subsidence, CFI, stem orientation, and CF. A χ 2 analysis was performed to compare complication rates between groups. Results: Subsidence was lower after placement of BFX lateral bolt stems (median, 0.24 mm; interquartile range [IQR; 1.49) compared with collared (1.27 mm [2.29]) and BFX (1.35 mm [2.26]) stems. No difference in subsidence was detected between collared and BFX implants. Coronal CF was greater after placement of BFX (mean ± SD, 0.72 ± 0.06) compared with lateral bolt (0.69 ± 0.05) or collared (0.66 ± 0.07) stems. Sagittal CF differed between all groups (BFX 0.7 ± 0.05, lateral bolt 0.67 ± 0.06, and collared 0.61 ± 0.06). No differences were identified in CFI or stem orientation in the coronal and sagittal planes or in complication rates between implants. Conclusion: The BFX lateral bolt femoral stem was associated with less postoperative subsidence compared with the BFX collared and traditional BFX stems. No consistent changes in CF, CFI, or stem orientation or complication rates were identified in association with increased subsidence in this study. Clinical significance: Implantation of a lateral bolt femoral stem should be considered during THR to prevent subsidence.